2010
DOI: 10.3892/or_00000814
|View full text |Cite
|
Sign up to set email alerts
|

BCL2L10 is frequently silenced by promoter hypermethylation in gastric cancer

Abstract: Abstract. In gastric cancer, several tumor suppressor and tumor-related genes are silenced by aberrant methylation. Previously, we demonstrated that BCL2L10, which belongs to the pro-apoptotic Bcl-2 family, was transcriptionally repressed by promoter hypermethylation and that its overexpression caused apoptosis and growth inhibition of gastric cancer cells. In this study, we investigated the methylation status of BCL2L10 and its expression in 21 gastric cancer tissues and corresponding non-neoplastic mucosae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mikata et al showed that BCL2L10, which belongs to the family of pro-apoptotic Bcl-2, is silenced by hypermethylation of the promoter. This study suggests that silencing BCL2L10 by methylation is a common feature in gastric cancer and may be involved in the early stages of gastric carcinogenesis (81). …”
Section: Epigenetic Changes Promote the Development Of Gastric Cancermentioning
confidence: 75%
“…Mikata et al showed that BCL2L10, which belongs to the family of pro-apoptotic Bcl-2, is silenced by hypermethylation of the promoter. This study suggests that silencing BCL2L10 by methylation is a common feature in gastric cancer and may be involved in the early stages of gastric carcinogenesis (81). …”
Section: Epigenetic Changes Promote the Development Of Gastric Cancermentioning
confidence: 75%
“…Additionally, patients with this BCL2L10 polymorphism have a diminished risk of the development de novo MDS [ 74 ]. Third, epigenetic regulation of Bcl-B has great significance in tumorigenesis: Methylation of the gene could lead to silenced or reduced expression of this protein in HCC [ 66 ] and gastric cancer [ 65 , 75 , 76 ]. Finally, a decrease in level of one antiapoptotic protein can be compensated for by an increase in the level of another prosurvival partner, a phenomenon that has been proved in various in vitro and in vivo models.…”
Section: Discovery Structure and Protein–protein Interactionsmentioning
confidence: 99%